Exploring Solomon's Paradox: Self-Distancing Eliminates the Self-Other Asymmetry in Wise Reasoning About Close Relationships in Younger and Older Adults. (August 2014) - Grossmann, Igor; Kross, Ethan
Are people wiser when reflecting on other people's problems compared with their own? If so, does self-distancing eliminate this asymmetry in wise reasoning? In three experiments ( N = 693), participants displayed wiser reasoning (i.e., recognizing the limits of their knowledge and the importance of compromise and future change, considering other people's perspectives) about another person's problems compared with their own. Across Studies 2 and 3, instructing individuals to s elf-distance (rather than self-immerse ) eliminated this asymmetry. Study 3 demonstrated that each of these effects was comparable for younger (20–40 years) and older (60–80 years) adults. Thus, contrary to the adage "with age comes wisdom, " our findings suggest that there are no age differences in wise reasoning about personal conflicts, and that the effects of self-distancing generalize across age cohorts. These findings highlight the role that self-distancing plays in allowing people to overcome a pervasive asymmetry that characterizes wise reasoning.